'Strangers in a strange land': Understanding professional challenges for human factors/ergonomics and healthcare. (July 2021) - Perry, Shawna J.; Catchpole, Kenneth; Rivera, A. Joy; Henrickson Parker, Sarah; Gosbee, John
Abstract: Human Factors and ergonomics (HFE) expertise continues to have difficulty integrating its experts into healthcare. This persistent disconnect is compounded by unique aspects of healthcare as an institution, industry and work system. Clinically-embedded HFE practitioners, a new HFE sub-specialty, are a conduit for addressing substantive mismatches between the two domains. Greater HFE penetration will require a fundamental change in stance for both domains, however, the burden will lie with HFE to be the more adaptive of the two. Learning more about the in situ work of this sub-specialty will provide insights for more nuanced approaches to bridging domain specific mismatches and obstacles. Highlights: Human Factors and ergonomics (HFE) expertise continues to have difficulty integrating its experts into healthcare. Clinically-embedded HFE practitioners are a conduit for addressing substantive mismatches in domain stance with healthcare. HFE must adapt and learn more about healthcare to ultimately create and engage in design moments in healthcare.